THE EFFECT OF CONSUMER ETHNOCENTRISM TOWARDS CONSUMER PREFERENCE: THE CASE OF GO-JEK - Mohamad, Dio Irsandi; Suharto, Yulianto (Journal of Business and Management, 2017)
Abstract. The rapid development of technology causing a demand to get access to get information quickly and as the result smartphone emerge as one of the solution to meet the demand. As the result of the increasing acceptance of smartphone usage worldwide with 93% of internet user in Indonesia accessing their internet via smartphone, mobile apps becoming a potential business in Indonesia. One of the local mobile apps that emerge is GO-JEK, an online transportation app with the concept of ridesharing. With this app user can meet with the owner of vehicle to get a ride to their destination. In this app category GO-JEK is the only local online transportation app compared to their foreign online transportation app competitor like Uber & Grab. All those apps expanding their features and products and slowly minimize the difference between them. The purpose of this study is to find out the factors influencing an online transportation app and focusing on what factors influencing consumer to prefer GO-JEK over its competitors. Attributes tested are Price Consciousness, Coupon Redemption, Innovativeness, Practicality, Safety, Trust, Comfort and Consumer Ethnocentrism. This study is a quantitative study and using convenience sampling as sampling techniques. There are 300 participants in the questionnaire coming from Jakarta and Bandung. The data then will be analyzed with Reliability Study, Descriptive Analysis and Logistic Regression. The result of this research are: 1. 52% of the respondents prefer to use GO-JEK over its competitors, 2. The attributes are accepted as a factors that influencing consumer preferences, and 3. Price Consciousness, Coupon Redemption, Safety, and Ã‚Â Keywords: Consumer Ethnocentrism, Consumer Preference, Online Transportation App